2017
DOI: 10.1093/mnras/stx962
|View full text |Cite
|
Sign up to set email alerts
|

Gas rotation, shocks and outflow within the inner 3 kpc of the radio galaxy 3C 33

Abstract: We present optical integral field spectroscopy -obtained with the Gemini Multi-Object Spectrograph -of the inner 4.0 × 5.8 kpc 2 of the narrow line radio galaxy 3C 33 at a spatial resolution of 0.58 kpc. The gas emission shows three brightest structures: a strong knot of nuclear emission and two other knots at ≈ 1.4 kpc south-west and northeast of the nucleus along the ionization axis. We detect two kinematic components in the emission lines profiles, with a "broader component" (with velocity dispersion σ 150 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…There are also detailed studies of radio galaxies in which the origin of the activity can be clearly attributed to a minor merger, the classical example being of Centarus A, which is estimated to have suffered such a merger a few 10 8 yr ago [63,64]. Other examples include Arp 102B, Pictor A and 3C 33 [65,66,67]. In the case of Pictor A, the inferred low metallicity of the gas further supports this conclusion.…”
Section: Minor Mergersmentioning
confidence: 78%
See 1 more Smart Citation
“…There are also detailed studies of radio galaxies in which the origin of the activity can be clearly attributed to a minor merger, the classical example being of Centarus A, which is estimated to have suffered such a merger a few 10 8 yr ago [63,64]. Other examples include Arp 102B, Pictor A and 3C 33 [65,66,67]. In the case of Pictor A, the inferred low metallicity of the gas further supports this conclusion.…”
Section: Minor Mergersmentioning
confidence: 78%
“…The AGNIFS group has also been obtaining masses for the ionized gas within the inner 100-500 pc, which are in the range (0.03 -8)×10 6 M [219] for low-luminosity AGN, while in more luminous ones -now within the inner kpc -these masses reach values of 10 8 − 10 9 M [221,67].…”
Section: Gas Masses and Mass Inflow Rates In The Near Universementioning
confidence: 99%
“…The origin of this effect is unclear. The high velocity dispersion could be due to interstellar material shocked by the expanding radio jet (Couto et al 2017) or to higher turbulence due to the presence of strong backflow toward the inner regions produced by the expansion of the radio cavity (e.g. Cielo et al 2017;Antonuccio-Delogu & Silk 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Integral field spectroscopic data provide us with a unique opportunity to study of the impact of AGN feedback in galaxies, mapping the distribution and the kinematics of the ionized gas with respect to the radio jet. Couto et al (2017) observed the radio galaxy 3C 033 with GEMINI-GMOS/IFU (over a field of view of 4 × 6 kpc 2 ) revealing complex motions, with signatures of inflow and outflows. In NGC 3393, a nearby Seyfert 2 galaxy with nuclear radio jets and a nuclear bar, Finlez et al (2018) with the same spectrograph found motions of rotation and outflows, traced by narrow emission line and broad component along the radio lobes and perpendicularly to them.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain the observed scaling relationships between the massaccreting supermassive black holes (SMBHs) and galaxy bulge properties (McConnell & Ma 2013;Kormendy & Ho 2013), AGN feedback is usually summoned (Fabian 2012). Although AGN feedback processes have been identified in recent works (Couto et al 2017;Revalski et al 2018), their impact must be quantified in order to determine whether or not they deliver effective power, capable of altering star formation rates and evacuating gas reservoirs (Harrison 2017;Zubovas & Bourne 2017).…”
Section: Introductionmentioning
confidence: 99%